Alfred Rosenberg : der Wegbereiter des Holocaust : eine Biographie - Koop, Volker 1945- (Böhlau Verlag, 2016)
Alfred Rosenberg came to the NSDAP very early, became one of its most important leaders and belonged to the thought leaders of the national socialist extermination policy. The biography by Volker Koop follows the career of the unscrupulous chief ideologist